Análise espacial da criminalidade no Espírito Santo e em Vitória - Pereira, André Luiz Greve (2010)
This dissertation investigates the determinants of crime in cities in the state of Espírito Santo and in the districts of its capital, Vitória. This study is based in the economic literature that seeks to identify the marginal impact of economic, social and demographic variables, as well as the marginal impact of apparently victimless crimes (drugs and guns crimes) on crimes with identifiable victims (homicide, offence against the person and crimes against property). The data used in this paper were criminal occurrences recorded by the Espírito Santo Department of Public Safety and Social Defense (SESP-ES), including criminals residences sorted at neighborhood level. This variable has no precedents in Brazilian economic studies. The results of the study emphasize the importance of the spillover effect in crime through two different channels: the influence of apparently victimless crimes in crimes against property and offences against the person, which had a greater explanatory power than social, economic and demographic variables; and a positive spatial correlation of crimes between cities. The public security policies are discussed and analyzed based on these results and the references consulted